2015
DOI: 10.4236/oje.2015.55015
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Population Dynamics of the Olive Fly, <i>Bactrocera oleae</i> Rossi. (Diptera, Tephritidae) in the Region of Essaouira

Abstract: The Bactrocera oleae Rossi fly is the most important olive pest. It is of major economic importance in the olive production area of Essaouira, where weather conditions are optimal for the conduct of the various stages of its life cycle. The lack of phytosanitary treatments worsens this situation. The development of the larval stages and different generations are related to the phenological stages of the olive and are controlled by changes in habitat conditions. Trapping of adult males by Deltas traps baited wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…It was followed by the third at the beginning of November and the fourth at the end of December. This succession of three generations in the autumn was similar to the results of Goncalves et al (2012) andAit Mansour et al (2015). However, Gaouar (1996) and Yokoyama et al (2006) found two generations in this period and Pertíñez & Vélez (2020) found only one generation in the fall.…”
Section: Study Of the Population Dynamics Of The Olive Flysupporting
confidence: 81%
“…It was followed by the third at the beginning of November and the fourth at the end of December. This succession of three generations in the autumn was similar to the results of Goncalves et al (2012) andAit Mansour et al (2015). However, Gaouar (1996) and Yokoyama et al (2006) found two generations in this period and Pertíñez & Vélez (2020) found only one generation in the fall.…”
Section: Study Of the Population Dynamics Of The Olive Flysupporting
confidence: 81%
“…Olive fruit fly, B. oleae had inactivity period from December to May. The data show that the hypogenous pupae wintering in the soil survive during winter and spring until June (Mansour et al, 2015). The life cycle of the olive fruit fly is synchronized with seasonal growth and olive fruit production (Zalom et al, 2009).…”
Section: Relation Of Soil Under Olive Trees To Resultant Populationsmentioning
confidence: 99%
“…Soil analysis show that the hypogenous pupae wintering in the soil survive until June. Knowledge of the factors involved in the bio-ecology of the olive fly and the phenology of the host allows the elaboration of monitoring/warning calendars, and phytosanitary measures in order to establish an IPM program adapted to the requirements of olive orchards in the region (Mansour et al, 2015). Currently collecting pupa under the trees and putting them in cages can give us the exactly time to start mass trapping in inactive period to suppress olive fruit fly populations before infestation seasons.…”
Section: Relation Of Soil Under Olive Trees To Resultant Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compare to the olive fruit fly's aggression mode, the control of this pest is all the more complex as conventional chemical control remains ineffective in controlling their damage and has harmful effects on the environment, producers and consumers. Faced with this situation and to improve the methods of fight against these pest, many studies around the world have been devoted to the knowledge of these insect in terms of their systematic, their biology, their ecology, their ethology and control (Boumezzough 2015, Nardi et al 2005, Vontas et al 2002, Alberola et al 1999, Katsoyannos et al 2001, Bueno et al 2002, Saour and Makee 2004, Kakani et al, 2010, Broumas et al al, 2002), particularly in algeria (Achouche, 2019, Senouci et al 2019, Medjkouh et al, 2018, Medjkouh et al, 2016, Ilias et al 2013, Tamendjari et al 2004.…”
Section: Introductionmentioning
confidence: 99%